PENGARUH PENERAPAN MODEL PEMBELAJARAN MEANS ENDS ANALYSIS(MEA)TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK DI KELAS XI MIA SMAN 1 PADANG TAHUN PELAJARAN 2018/2019 - Muhammad Syahrul (Departemen Matematika, 2019)
Mathematical problem solving skills is ones of mathematics learning goal that expected in School. Studentsare expected to have the good mathematical problem solving skills. However, the result of tests that have been conducted at 1 Padang senior high school shows that students have low mathematical problem solving skills. This mattercan be improved by implementing Means Ends Analysis learning models to the learning process in the school.This research aims to find out whether the mathematical problem solving skills of students who follow the learning MEA model are better than those who follow the convensional learning. This research is quasy experiment research with static group design. The result of the final tests shows that the mathematical problem solving skill of students who followed the MEA learning modelhave increased. Besides, the results of hypothesis test shows that the mathematical problem solving skills of students who follow the learning MEA model are better than those who follow the convensional learning. Thus the MEA learning model influences student’s mathematical problem solving skill. Keywords— The Mathematical Problem Solving Skills, Means Ends Anlaysis Learning Models, Conventional Learning Models.